P3.223 HPV Genotype Distribution in HIV-Positive African Women and Associations with High Grade Histological Lesions by CD4+ Count. (13th July 2013) - Kelly, H; Ngou, J; Sawadogo, B; Muzah, B; Gilham, C; Nagot, N; Meda, N; Delany, S; Segondy, M; Mayaud, P
Abstract : Background: To assess the prevalence, genotype distribution and risk factors for high-risk HPV among HIV-positive African women, and associations with cervical histological lesions. Methods: The HARP study enrolled HIV-positive women aged 25–50 in Burkina Faso (BF) and South Africa (SA). A stratified sampling strategy was used, with 2/3 of women on ART. Cervical HPV genotyping was performed using InnoLipa. Four-quadrant cervical biopsies were obtained among women with abnormalities detected by at least one test or by colposcopy. Results: 628 and 624 women were enrolled in BF and SA, respectively. The distribution of CD4+ count (cells/µL) was similar in both sites: 68% with CD4+ ≥ 350 and 10% with CD4+ < 200. Prevalence of HR-HPV genotypes was 62% among women in BF and 78% in SA, and, overall, 67%, 73% and 84% among women with CD4+ ≥ 350, 200–349 and < 200, respectively (Table). The 4 most common genotypes in BF were HPV52 (20%), HPV51 (12%), HPV35 (9%), HPV66 (8%); and in SA, HPV52 (24%), HPV16 (15%), HPV51 (14%) and HPV35 (14%). Multiple types were observed in 41% and 55% of HR-HPV-positive women in BF and SA, respectively; and increased with decreasing CD4 count (46%, 52% and 63%, respectively, P-trend = 0.004). HPV types 58, 33 and 16 were most strongly associated with CIN2+ (OR = 5.06, OR = 4.62, OR = 4.02) and types 16, 35 and 58 were most strongly associated with CIN3+ (OR = 4.59, OR = 3.36, OR = 2.96). Decreasing CD4+ count and younger age were associated with higher HR-HPV prevalence in both countries (Table). Multiple sex partners, smoking and lower income were also significantly associated with HR-HPV in SA. Conclusions: HR-HPV prevalence is high among HIV-positive women with genotype distribution similar in both countries. HR-HPV prevalence is associated with young age and lower CD4+ count. Whilst HPV52 is the most prevalent type, HPV16 is most strongly associated with increasing lesion severity.